2014
DOI: 10.1038/ncomms6112
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing the formation and relaxation of dressed quasi-particles in a strongly correlated electron system

Abstract: The non-equilibrium approach to correlated electron systems is often based on the paradigm that different degrees of freedom interact on different timescales. In this context, photo-excitation is treated as an impulsive injection of electronic energy that is transferred to other degrees of freedom only at later times. Here, by studying the ultrafast dynamics of quasi-particles in an archetypal strongly correlated charge-transfer insulator (La 2 CuO 4 þ d ), we show that the interaction between electrons and bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 54 publications
14
72
0
Order By: Relevance
“…No physical correction of the chirp of the broadband white light pulses was performed, but a post-processing correction of the chirp was applied to the data. Corrections to compensate the mismatch between the penetration depths at the pump photon-energy and at the various probe photon-energies (as described by Novelli et al 28 ) have been found not to be significant. The experiment was performed with the sample at 35 K, 80 K, and 140 K, the latter one being above the Verwey transition temperature.…”
Section: Methodsmentioning
confidence: 99%
“…No physical correction of the chirp of the broadband white light pulses was performed, but a post-processing correction of the chirp was applied to the data. Corrections to compensate the mismatch between the penetration depths at the pump photon-energy and at the various probe photon-energies (as described by Novelli et al 28 ) have been found not to be significant. The experiment was performed with the sample at 35 K, 80 K, and 140 K, the latter one being above the Verwey transition temperature.…”
Section: Methodsmentioning
confidence: 99%
“…One of the prototypical targets for the nonequilibrium many-body systems is the Mott insulator and the carrier-doped Mott insulator. A variety of exotic nonequlibrium phenomena emerges owing to the spin and orbital degrees of freedom, [3][4][5][6][7][8][9][10][11] and a number of theoretical studies has been also performed in the optical induced nonequilibrium state in the Mott insulators. [12][13][14][15][16][17][18][19][20][21] Another promising target for the photoinduced nonequilibrium dynamics in correlated electron systems is the charge ordered (CO) state, in which the averaged electron density per site is 0.5 in most of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…By shining the sample with intense ultrafast pulses (pump) one can trigger nonequilibrium transient states, whose physical properties are then recorded by a second pulse (probe) which hits the sample with a given time delay. This approach opens up a wealth of information unavailable to conventional time-averaged spectroscopies [1][2][3][4][5][6][7][8][9]. When used in combination with angle-resolved photoemission spectroscopy (ARPES), these ultrafast methods allow us to track and follow in real time the evolution of quasiparticle modes in different momentum sectors, such as those close to the gap nodes and antinodes of d-wave cuprate superconductors [10][11][12].…”
mentioning
confidence: 99%